Job stress, burnout and coping in police officers: Relationships and psychometric properties of the organizational police stress questionnaire - Queirós, Cristina (2020)
Policing is a stressful occupation, which impairs police officers’ physical/mental health and elicits burnout, aggressive behaviors and suicide. Resilience and coping facilitate the management of job stress policing, which can be operational or organizational. All these constructs are associated, and they must be assessed by instruments sensitive to policing idiosyncrasies. This study aims to identify operational and organizational stress, burnout, resilient coping and coping strategies among police officers, as well to analyze the psychometric properties of a Portuguese version of the Organizational Police Stress Questionnaire. A cross-sectional study, with online questionnaires, collected data of 1131 police officers. With principal components and confirmatory factor analysis, PSQ-org revealed adequate psychometric properties, despite the exclusion of four items, and revealed a structure with two factors (poor management and lack of resources, and responsibilities and burden). Considering cut-off points, 88.4% police officers presented high operational stress, 87.2% high organizational stress, 10.9% critical values for burnout and 53.8% low resilient coping, preferring task-orientated than emotion and avoidance coping. Some differences were found according to gender, age and job experience. Job stress and burnout correlated negatively with resilient coping, enthusiasm towards job and task-orientated coping. Results reinforce the importance to invest on police officers’ occupational health.